Assessment of candidate immunohistochemical prognostic markers of meningioma recurrence - Csonka, Tamás; Murnyák, Balázs; Szepesi, Rita; Bencze, János; Bognár, László; Klekner, Álmos; Hortobágyi, Tibor (Folia Neuropathologica, 2016)
Although tumour recurrence is an important and not infrequent event in meningiomas, predictive immunohistochemical markers have not been identified yet. The aim of this study was to address this clinically relevant problem by systematic retrospective analysis of surgically completely resected meningiomas with and without recurrence, including tumour samples from patients who underwent repeat surgeries. Three established immunohistochemical markers of routine pathological meningioma work-up have been assessed: the proliferative marker Ki-67 (clone Mib1), the tumour suppressor gene p53 and progesterone receptor (PR). All these proteins correlate with the tumour WHO grade, however the predictive value regarding recurrence and progression in tumour grade is unknown. One hundred and fourteen surgical specimens of 70 meningioma patients (16 male and 54 female) in a 16 years’ interval have been studied. All tumours had apparently complete surgical removal. On Mib1, PR and p53 immunostained sections, the percentage of labelled tumour cells, the staining intensity and the multiplied values of these parameters (the histoscore) was calculated. Results were statistically correlated with tumour WHO grade, (sub)type, recurrence and progression in WHO grade at subsequent biopsies. Our results confirmed previous findings that the WHO grade is directly proportional to Mib1 and p53 and is inversely proportional to the PR immunostain. We have demonstrated that Mib1 and p53 have a significant correlation with and predictive value of relapse/recurrence irrespective of the histological subtype of the same WHO grade. As a quantitative marker, Mib1 has the best correlation with a percentage of labelled cells, whereas p53 with intensity and histoscore. In conclusion, the immunohistochemical panel of PR, p53, Mib1 in parallel with applying standard diagnostic criteria based on H&E stained sections is sufficient and reliable to predict meningioma recurrence in surgically completely resected tumours.